Are sarcopenia, obesity and sarcopenic obesity predictive of outcome in patients with colorectal liver metastases?. Issue 5 (16th December 2014) - Lodewick, Toine M.; van Nijnatten, Thiemo J. A.; van Dam, Ronald M.; van Mierlo, Kim; Dello, Simon A. W. G.; Neumann, Ulf P.; Olde Damink, Steven W. M.; Dejong, Cornelis H. C.
Abstract Background The impact of body composition on outcomes after surgery for colorectal liver metastases (CRLM) remains unclear. The aim of the present study was to determine the influence of sarcopenia, obesity and sarcopenic obesity on morbidity, disease‐free (DFS) and overall survival (OS). Method Between 2005 and 2012, all patients undergoing a partial liver resection for CRLM in the Maastricht University Medical Centre, and who underwent computed tomography (CT) imaging within 3 months before liver surgery, were included. Body composition was primarily based on pre‐operative CT measurements. Sarcopenia was based on total muscle area at the level of the third lumbar vertebra and predefined body mass index (BMI)‐ and gender‐specific cut‐off values for sarcopenia were used. Body fat percentages were calculated and the top 40% for men and women were considered obese. Results Of the 171 included patients undergoing liver surgery for CRLM, 80 (46.8%) patients were sarcopenic, 69 (40.4%) obese and 49 (28.7%) sarcopenic obese. The presence of sarcopenia, obesity or sarcopenic obesity did not affect the complication rates. However, readmission rates were significantly increased in patients with (sarcopenic) obesity (P < 0.05). Surprisingly, obesity seemed to prolong OS (P = 0.021) and was identified as an independent predictor [hazard ratio (HR):0.58 and P = 0.046] for better OS. Sarcopenia and sarcopenic obesity did not affect DFS or OS. Conclusion Sarcopenia, obesity and sarcopenic obesity did not worsen DFS, OS and complication rates after a partial liver resection for CRLM.